Relevance of Anti-HLA Antibody Strength Underestimation in Single Antigen Bead Assay for Shared Eplets. Issue 12 (11th July 2022) - Claisse, Guillaume; Devriese, Magali; Lion, Julien; Maillard, Nicolas; Caillat-Zucman, Sophie; Mooney, Nuala; Taupin, Jean Luc
Abstract : Background: HLAs contain combinations of multiple eplets, sometimes shared between numerous HLA alleles. Some authors suggested that single antigen bead (SAB) assays may underestimate the signal of anti-HLA antibodies (Ab) when several beads share the targeted eplet. However, this assumption has not yet been validated experimentally. Methods: We selected 5 eplets shared by 1–24 beads of the routine SAB kits: the eplet 163LS/G; the 3 eplets 127K, 62GE, and 62GRN thereafter called cross-reactive group 2C; the 82LR eplet, well-known as Bw4; the locally called QB2A5 eplet associated with the DQA1*05:01/DQB1*02:01 combination; and the 40GR DQ eplet. We selected a dozen of sera for each eplet with Ab mean fluorescence intensity (MFI) between 1000 and 15 000 for the beads carrying the targeted eplet. We tested them with the classical SAB panel (SABp), with an isolated bead carrying the eplet (isolated SAB [SABi]) and with a mixture of both (SABp+i). Results: No significant difference in MFI was detected among SABi, SABp, and SABp+i conditions for all the eplets. Conclusions: We noticed only a nonsignificant difference in the Ab MFI signal due to eplet sharing on the SAB assay. We, therefore, conclude that this phenomenon should no longer be considered as a significant risk factor during patient follow-up pre- or posttransplantation.